2009
DOI: 10.1002/app.30902
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of CMCS/PVA blend membranes and its sorption and pervaporation performance (I)

Abstract: Novel pervaporation (PV) membranes for ethanol dehydration were prepared by blend poly(vinyl alcohol) (PVA) and carboxymethyl chitosan (CMCS), followed by the crosslinking reaction with glutaraldehyde; the structure and miscibility of the blend membranes were characterized by Fourier transform infrared, X-ray diffraction, and differential scanning calorimetry; the results indicated that the blends were miscible. The effect of feed concentration, operation temperature, crosslinking agent content, etc. on sorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…Compared to other modification technologies or new preparation materials, blending of polymers is preferred for membrane synthesis [11]. In our previous work, a CMCS/poly (vinyl alcohol) (PVA) blend membrane was prepared for pervaporation [12]. The prepared membrane displayed a good separation performance for ethanol/water mixtures because the membrane possesses many hydroxyl and carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other modification technologies or new preparation materials, blending of polymers is preferred for membrane synthesis [11]. In our previous work, a CMCS/poly (vinyl alcohol) (PVA) blend membrane was prepared for pervaporation [12]. The prepared membrane displayed a good separation performance for ethanol/water mixtures because the membrane possesses many hydroxyl and carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical crosslinks are not as strong or stable as chemical crosslinks . PVA can be chemically crosslinked by acetalization with formaldehyde and glutaraldehyde or by esterification with L‐malic acid, citric acid, and fumaric acid . These aldehydes are volatile and need to consume a certain level of catalyst during the process of acetalization treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nawawi and Huang [4] however concluded that chitosan has a reasonably poor stability in water and in aqueous mixtures due to the amino group in its structure. Various modification techniques have been applied namely crosslinking [5,6], blending [7] and incorporation of zeolite [8,9] in order to improve overall properties of chitosan as well as its separation performance. Blending is the most common modification method applied as it provides a convenient way of developing materials with novel or selectively enhanced properties which are possibly superior to those of the components, besides offering the possibility in tailoring endproducts' properties [2,5,6,7,8].…”
Section: 10 Introductionmentioning
confidence: 99%